2022
DOI: 10.1039/d1ra08021k
|View full text |Cite
|
Sign up to set email alerts
|

Structural effect of Ni/TiO2 on CO methanation: improved activity and enhanced stability

Abstract: Highly dispersed Ni/TiO2 catalyst with Ni (111) obtained by cold plasma decomposition shows improved activity and carbon resistance for CO methanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, obtaining a supported Ni catalyst with a desired structure remains a significant challenge. Only a few studies can be found in the literature on the preparation of catalysts with Ni (111) as the principal exposed face using specific preparation methodologies, such as cold plasma, 87,88,102,111–114 external magnetic field assisted reduction 115 and electrospinning, 116 or using specific supports. 117,118 Fig.…”
Section: Co2 Hydrogenation To Methanementioning
confidence: 99%
“…However, obtaining a supported Ni catalyst with a desired structure remains a significant challenge. Only a few studies can be found in the literature on the preparation of catalysts with Ni (111) as the principal exposed face using specific preparation methodologies, such as cold plasma, 87,88,102,111–114 external magnetic field assisted reduction 115 and electrospinning, 116 or using specific supports. 117,118 Fig.…”
Section: Co2 Hydrogenation To Methanementioning
confidence: 99%